Linking N(2)O emission from biochar-amended composting process to the abundance of denitrify (nirK and nosZ) bacteria community - Li, Shuqing (AMB Express, 2016)
Manure composting has been recognized as an important anthropogenic source of nitrous oxide (N(2)O) contributing to global warming. However, biochar effect on N(2)O emissions from manure composting is rarely evaluated, especially by linking it to abundance of denitrifying bacteria community. Results of this study indicated that biochar amendment significantly reduced N(2)O emissions from manure composting, primarily due to suppression of the nirK gene abundance of denitrifying bacteria. Pearson’s correlation analysis showed a significant positive correlation between nirK abundance and N(2)O fluxes, while a negative correlation between nosZ density and N(2)O fluxes. Simultaneously, a linear correlation between nirK gene abundance minus nosZ gene abundance with N(2)O fluxes was also observed. In addition, a statistical model for estimating N(2)O emissions based on the bacterial denitrifying functional genes was developed and verified to adequately fit the observed emissions. Our results highlighted that biochar amendment would be an alternative strategy for mitigating N(2)O emissions during manure composting, and the information of related functional bacterial communities could be helpful for understanding the mechanism of N(2)O emissions.